Physical Glitch Music. - ZAREEI, MOH.; CARNEGIE, DALE A.; KAPUR, AJAY (Leonardo Music Journal, 2015)
This article introduces an ensemble of mechatronic sound-sculptures designed and developed to realize glitch music outside of computers; the sculptures instead create glitches mechanically, physically and visibly. A brief description of the three different instrument types forming the ensemble is followed by a discussion of how the sound-sculptures employ a Brutalist "anti-beauty" approach in terms of both design and ideology.